Study of the radiation pattern of a rectangular horn antenna in the operation of multimode propagation of electromagnetic waves - Semenov, Andriy; Semenova, Olena; Pinaiev, Bogdan; Kozin, Dmytro; Shpylovyi, Oleksandr (Technology audit and production reserves, 2022)
The object of research in the work is the process of radiation of electromagnetic waves and the directional properties of a rectangular horn antenna in a multimode operation. The existing problem is that in practice when developing and researching horn antennas, only the single-mode mode of their operation is taken into account. The fundamental mode of the rectangular waveguide that feeds this horn antenna is chosen as the base mode of the emitted electromagnetic wave. Radiation of higher types of electromagnetic waves is not taken into account. To take into account the impact of higher types of electromagnetic waves on the directional properties of a rectangular horn antenna, it is proposed to investigate a multimode mode consisting of three types of magnetic waves H10, H20, and H30. Horn antennas have high-quality wide-range properties and make it possible to obtain a maximum frequency coverage ratio of 1.5–1.8. In this paper, the directional properties of a rectangular horn antenna are determined by the example of calculating and modeling normalized radiation patterns of a standard horn-type for a wide frequency range with an average frequency of 12 GHz and a frequency overlap factor of 1.67. It has been established that when emitting three higher types of waves, it is possible to simultaneously improve the characteristics and directional properties of a horn antenna by changing the amplitude of each component of the constituent waves of electromagnetic radiation. The work aimed to study the normalized radiation patterns of a rectangular horn antenna to improve its directional properties. It was found that with increasing frequency, starting from the middle frequency of the operating frequency range, the radiation pattern of a rectangular horn antenna expanded. That is, the opening angle increased in the direction of the main radiation, with a decrease in the radiation amplitude, the level of the side and rear lobes increased, which leads to a deterioration in the characteristics of the horn antenna. For the selected geometric dimensions of the horn antenna in the frequency range of 12–12.5 GHz in the multimode mode, it was possible to provide almost the same beam width in the horizontal and vertical planes at the level of 13.2–13.6°.